2018
DOI: 10.1108/rbf-07-2017-0070
|View full text |Cite
|
Sign up to set email alerts
|

Corporate risk and the humpback of CEO narcissism

Abstract: Purpose -The purpose of this paper is to investigate the association between CEO narcissism and corporate risk taking. Design/methodology/approach -The authors provide a novel and unobtrusive measure of CEO narcissism based on LinkedIn profiling. The authors investigate the relationship between CEO narcissism and corporate risk taking (stock return volatility) for a sample of 475 US manufacturing firms in the period 2010-2014. Findings -The authors find an inverse U-shape relationship between CEO narcissism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 50 publications
0
19
0
1
Order By: Relevance
“…The vulnerable side of narcissism could have altered the results. Thus, Aabo and Eriksen (2018) show that very narcissistic CEOs take less risk than moderately narcissistic CEOs. Furthermore, Aabo et al (2020) show that a high amount of narcissistic supply (large firm and high compensation) moderates the risk taking by narcissistic CEOs.…”
Section: Ceo Narcissism and Corporate Acquisitionsmentioning
confidence: 88%
See 1 more Smart Citation
“…The vulnerable side of narcissism could have altered the results. Thus, Aabo and Eriksen (2018) show that very narcissistic CEOs take less risk than moderately narcissistic CEOs. Furthermore, Aabo et al (2020) show that a high amount of narcissistic supply (large firm and high compensation) moderates the risk taking by narcissistic CEOs.…”
Section: Ceo Narcissism and Corporate Acquisitionsmentioning
confidence: 88%
“…Narcissistic CEOs are not risk seekers per se (Aabo and Eriksen, 2018). Thus, Jauk et al (2017) find that high levels of grandiose narcissism are likely to be accompanied by narcissistic vulnerability and Gore and Widiger (2016) find that grandiose narcissists are likely to display episodes of vulnerable narcissism.…”
Section: Introductionmentioning
confidence: 98%
“…Both measures are stable across the 10-yr period with yearly average ranges of 0.25-0.27 and 2.19-2.24, respectively (with a small downward trend, if any). The alternative measure for CEO narcissism based on press releases was used by Chatterjee and Hambrick (2007) in their index for CEO narcissism and has subsequently been used by Chatterjee and Hambrick (2011); Aabo and Eriksen (2018), among others. The press release is an instrument for the CEO to tell the investors, analysts, media, etc.…”
Section: Robustness Testsmentioning
confidence: 99%
“…In this regard, there have been a number of recent studies looking at the dark-side and corporate affairs. Aabo and Erikson (2018) hypothesized and demonstrated that there is an inverse U relationship between a CEO's Narcissism and company stock return volatility. In short, Narcissists take more risks which can be both advantageous and disadvantageous depending on the situation.…”
Section: Conscientiousnessmentioning
confidence: 99%